Section 4: Clinical Pharmacy Services 2019
DOI: 10.1136/ejhpharm-2019-eahpconf.225
|View full text |Cite
|
Sign up to set email alerts
|

4CPS-076 Encouraging the responsible use of antibiotics: awareness and understanding among a university student population of a community pharmacy public health campaign in scotland

Abstract: The result of the analysis confirms an increase in appropriateness of 7.51%.In the two periods compared, there was an increase in reports that also produced an economic saving of C ¼ 33,619.12. Conclusion The analysis shows that the role of the pharmacist is fundamental, both to ensure the effectiveness and efficiency of the therapies and to limit the costs of pharmaceuticals and health in general. REFERENCES AND/OR ACKNOWLEDGEMENTShttps://www.researchgate.net/publication/273647155_DD-007_Is_the_Unit_Dose_Proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…In the present study, 63% of participants had heard about MDR pathogens, lower than the percentage reported by a study in Germany (94.9%) and in Scotland (86%) ( Raupach-Rosin et al, 2019 ; Tonna et al, 2019 ). Very few of our respondents reported having been diagnosed with MDR pathogens (12%) or knowing someone infected with an MDR pathogen (7.3%), unlike the 42.7% reported to be acquainted with a person diagnosed with MDR pathogen in Germany or the 32.0% reported to be acquainted with a person diagnosed with methicillin-resistant Staphylococcus aureus in Scotland ( Raupach-Rosin et al, 2019 ; Tonna et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In the present study, 63% of participants had heard about MDR pathogens, lower than the percentage reported by a study in Germany (94.9%) and in Scotland (86%) ( Raupach-Rosin et al, 2019 ; Tonna et al, 2019 ). Very few of our respondents reported having been diagnosed with MDR pathogens (12%) or knowing someone infected with an MDR pathogen (7.3%), unlike the 42.7% reported to be acquainted with a person diagnosed with MDR pathogen in Germany or the 32.0% reported to be acquainted with a person diagnosed with methicillin-resistant Staphylococcus aureus in Scotland ( Raupach-Rosin et al, 2019 ; Tonna et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 92%
“…This suggests that information for the general public should be tailored for comprehensibility. Gaps in specific knowledge about the implications of MDR pathogens and existing treatment options have been observed before ( Tonna et al, 2019 ; McClelland et al, 2022 ). Hence, targeting information to the population and using appropriate media are essential for increasing the public’s knowledge of proper antibiotic use and MDR pathogens.…”
Section: Discussionmentioning
confidence: 99%